Accuracy of the Securetec DrugWipe 6s Ketamine device in detecting acute and residual salivary ketamine following a stepwise intravenous treatment protocol. Issue 1 (2nd January 2020) - Hayley, Amie C.; Green, Maja; Keane, Michael; Kostakis, Panagiota; Shehabi, Yahya; Stough, Con K. K.; Downey, Luke A.
Abstract: To evaluate the sensitivity of the Securetec DrugWipe 6 S Ketamine device in detecting salivary ketamine, we administered three fixed, increasing sub-anaesthetic doses of intravenous ketamine solution to 20 participants using an open-label, within subjects' protocol. Results indicated, at a cut-off level of 5 ng/mL for ketamine in oral fluid, the Securetec DrugWipe 6 S Ketamine device indicated a uniformly positive result for the presence of ketamine during the acute dosing phase where corresponding mean whole blood ketamine concentrations were 0.38 mg/L (dose 1), 0.48 mg/L (dose 2) and 0.82 mg/L (dose 3), respectively. At 2-hours post treatment, the positive detection rate was 85% where corresponding mean whole blood concentrations of ketamine were 0.21 mg/L. Device detection rate reduced to 40% at 4-hours post-treatment.